2015
DOI: 10.1088/0952-4746/35/2/429
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures to radiofrequency fields: results of an Israeli national survey

Abstract: Relatively high exposures to radiofrequency (RF) fields can occur in the broadcast, medical, and communications industries, as well in occupations that use RF emitting equipment (e.g. law enforcement). Information on exposure to workers employed in these industries and occupations is limited. We present results of an Israeli National Survey of occupational RF field levels at frequencies between ~100 kHz and 40 GHz, representing Industrial Heating, Communications, Radar, Research, and Medicine. Almost 4300 meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Previous measurements in telecom and broadcasting have indicated that routine exposure is generally low 16 and though some spot measurements around the VHF antennas did exceed 100 V m −1 these were made at the rear of antennas close to steelwork where re-radiation can occur or at splitters where leakage was acknowledged. All of these measurements were made in the highly localised conditions of near-field radiation and are not necessarily indicative of whole-body exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous measurements in telecom and broadcasting have indicated that routine exposure is generally low 16 and though some spot measurements around the VHF antennas did exceed 100 V m −1 these were made at the rear of antennas close to steelwork where re-radiation can occur or at splitters where leakage was acknowledged. All of these measurements were made in the highly localised conditions of near-field radiation and are not necessarily indicative of whole-body exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally occupational exposures have been assessed through the measurement of electric and magnetic field strength using portable hazard survey instrumentation 23 25 . However, the worker's exposure depends on the source's power, modulation scheme and field pattern, as well as the worker's behaviour and adherence to proper safety practice 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peak values of 10-g average local SARs were calculated in various situations and found bellow 2 W/kg from distances of 8 cm onward. Analyzing the practical use of portable transceivers by professionals over a national survey focused on various occupations, in the article published in 2015 by an Israelian group [14], the authors concluded that the cumulative collective exposures over all workers within an occupation, portable transceivers exposure dominated with 96% of the total, conducting to field levels exceeding safe limits for incident field strengths and also to the highest SARs among all RF sources. In this regard, present approach aimed at presenting a series of dosimetric results coming from tests made in an accredited laboratory with one model of dual-band portable transceiver emitting in the UHF band and with a model of walkie-talkie, both emitting on the same frequency, for comparison of the results.…”
Section: Introductionmentioning
confidence: 99%